A kind of mordenite and its synthesis method
Through the second-order crystallization reaction method, combined with the introduction of sulfate and lignin sulfonate, mordenite with micron nanocomposite characteristics was successfully synthesized, solving the problem that material performance is affected by the differences in the pore diffusion paths in the prior art, and achieving the improvement of the material's performance in adsorption and catalysis.
Patent Information
- Application Number
- CN202210103836.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-28
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-01-28
AI Technical Summary
It is difficult to synthesize mordenites with micron nanocomposite properties in the prior art, and there are differences in the pore diffusion pathways during adsorption and catalysis, which affects the performance of the material.
The second-order crystallization reaction method is adopted, first heat treatment and aging treatment are performed under contact conditions, followed by first-order crystallization reaction, and sulfate and lignin sulfonate are introduced in the second-order crystallization reaction to regulate the reaction temperature and time to control the nucleation and growth of mordenite.
The successful synthesis of mordenite with micron nanocomposite properties has improved the adsorption and catalytic performance of the material and provided a unique pore structure to enhance the application effect of the material.
Smart Images

Figure CN116553570B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic materials and relates to a molecular sieve synthesis method, in particular to mordenite and a synthesis method thereof. Background Art
[0002] Mordenite is a macroporous molecular sieve with two-dimensional pores. It has excellent heat resistance, acid resistance and water vapor resistance. It is widely used in industry as an adsorbent for separation of gas or liquid mixtures and as a catalyst in petrochemical and fine chemical industries.
[0003] CN1524788A discloses a method for synthesizing zinc-containing MOR zeolite, which comprises the steps of uniformly mixing water glass and fluoride, adding aluminum source and zinc source, stirring evenly, and crystallizing at 120-220°C statically or dynamically for 1-6 days to finally obtain zinc-containing MOR zeolite.
[0004] CN108217680A discloses a method for synthesizing mordenite MOR molecular sieve, and its products and applications. The method is characterized in that additional reagents with different structures and charge densities and optional fluorination reagents are introduced into the synthetic gel, and the acid center of the obtained MOR zeolite B is preferentially located in the "side pocket" of the 8-membered ring connected to the 12-membered ring channel.
[0005] CN106698453A discloses a method for synthesizing nano-MOR molecular sieves. The method first prepares a structure directing agent, then mixes alkali, aluminum source, silicon source, structure directing agent and water to prepare a synthetic gel, mixes the gel with macroporous carbon, performs ultrasonic treatment, and then puts the gel into a reactor for crystallization reaction. The obtained solid product is filtered, washed, dried and calcined to obtain a nano-MOR molecular sieve.
[0006] CN105366689A discloses a method for synthesizing a MOR zeolite molecular sieve membrane with microwave assistance in a dilute solution. The method comprises the following steps: dispersing MOR zeolite molecular sieve seeds in deionized water to obtain a MOR zeolite molecular sieve seed solution; introducing the molecular sieve seed solution into a seed layer on the surface of a porous carrier; dissolving NaOH, an Al source, a Si source and NaF in deionized water to prepare a synthesis solution; placing a porous carrier loaded with the MOR zeolite molecular sieve seeds in the synthesis solution, synthesizing by microwave heating, and after the synthesis reaction is completed, taking out the tube, washing and drying the MOR zeolite molecular sieve membrane with deionized water. Summary of the invention
[0007] In view of some problems in the prior art, the main purpose of the present invention is to provide a mordenite and a synthesis method thereof, which can synthesize mordenite with micron-nano composite properties.
[0008] The first aspect of the present invention provides a mordenite, which is a rectangular parallelepiped crystal with a length of 500-1500nm, a width of 50-100nm and a thickness of 30-60nm; the crystal has micron characteristics in the length direction and nanometer characteristics in the width and thickness directions, wherein main pores of the mordenite are distributed in the length direction of the crystal, and the size of the main pores is 0.65×0.70nm, and secondary pores of the mordenite are distributed in the width direction of the crystal, and the size of the secondary pores is 0.26×0.7nm.
[0009] Furthermore, the total specific surface area of the above-mentioned mordenite is 300 to 500 m 2 / g, pore volume is 0.1~0.4cm 3 / g,
[0010] Furthermore, the mordenite has a concentrated mesopore distribution, and the most probable pore diameter is 15 to 30 nm.
[0011] The second aspect of the present invention provides a method for synthesizing mordenite, comprising the following contents:
[0012] (1) Under contact conditions, mordenite seed crystals, inorganic alkali and water are mixed for heat treatment, and after cooling to 20-30° C., silicon source and aluminum source are added for aging treatment;
[0013] (2) heating the material obtained after the aging treatment in step (1) to perform a first-order crystallization reaction;
[0014] (3) After the first-order crystallization reaction is completed and the temperature is lowered to 10-30°C, sulfate and lignin sulfonate are added and the temperature is raised to carry out a second-order crystallization reaction, and then the mordenite is obtained by separation and drying.
[0015] Furthermore, in the above-mentioned method for synthesizing mordenite, the inorganic base in step (1) is one or more of sodium hydroxide and potassium hydroxide.
[0016] Furthermore, in the above-mentioned method for synthesizing mordenite, the heat treatment in step (1) is carried out at 100-200° C. for 1-5 hours.
[0017] Furthermore, in the above-mentioned method for synthesizing mordenite, the aluminum source in step (1) can be selected from one or more of aluminum sulfate, sodium aluminate, aluminum chloride, and aluminum nitrate, preferably aluminum chloride and / or aluminum nitrate.
[0018] Furthermore, in the above-mentioned method for synthesizing mordenite, the silicon source in step (1) is selected from one or more of silica gel, white carbon black, silica sol, and water glass.
[0019] Furthermore, in the above-mentioned method for synthesizing mordenite, the molar ratio of the inorganic base, silicon source (calculated as SiO2), aluminum source (calculated as A12O3) and water in step (1) is 2-12 inorganic base: 18-90 SiO2: A12O3: 800-2300 H2O, preferably 3-10 inorganic base: 20-80 SiO2: A12O3: 1000-2000 H2O.
[0020] Furthermore, in the above-mentioned method for synthesizing mordenite, the aging treatment temperature in step (1) is 10 to 50° C., preferably 20 to 40° C.; and the aging treatment time is 2 to 15 hours, preferably 5 to 10 hours.
[0021] Furthermore, in the above-mentioned method for synthesizing mordenite, the mass ratio of the mordenite seed crystals to the silicon source in step (1) is 0.5 to 12:100, preferably 1 to 10:100.
[0022] Furthermore, in the above-mentioned method for synthesizing mordenite, the reaction temperature of the first-stage crystallization reaction in step (2) is 140-200° C., preferably 150-190° C.; and the first-stage crystallization reaction time is 3-12 h, preferably 5-10 h.
[0023] Furthermore, in the above-mentioned method for synthesizing mordenite, the lignin sulfonate in step (3) can be at least one of sodium lignin sulfonate and potassium lignin sulfonate.
[0024] Furthermore, in the above-mentioned method for synthesizing mordenite, the sulfate in step (3) is at least one of sodium sulfate, potassium sulfate, iron sulfate, copper sulfate and magnesium sulfate, preferably at least one of sodium sulfate and potassium sulfate.
[0025] Furthermore, in the above-mentioned method for synthesizing mordenite, the mass ratio of the lignin sulfonate to the silicon source in step (3) is 0.03 to 0.15:1, preferably 0.05 to 0.1:1.
[0026] Furthermore, in the above-mentioned method for synthesizing mordenite, the mass ratio of the sulfate to the silicon source in step (3) is 0.15 to 0.25:1, preferably 0.1 to 0.2:1.
[0027] Furthermore, in the above-mentioned method for synthesizing mordenite, the reaction temperature of the second-order crystallization reaction in step (3) is 130-190° C., preferably 140-180° C.; the second-stage reaction time is 15-55 h, preferably 17-50 h.
[0028] Furthermore, in the above-mentioned method for synthesizing mordenite, the reaction temperature of the second-stage crystallization reaction in step (3) is 5 to 25° C. lower than the reaction temperature of the first-stage crystallization reaction in step (2), and preferably 10 to 20° C. lower.
[0029] Furthermore, in the above-mentioned method for synthesizing mordenite, the separation in step (3) can be carried out by centrifugation, filtration and the like, preferably by filtration, which is generally carried out multiple times, usually 1 to 10 times.
[0030] Furthermore, in the above-mentioned method for synthesizing mordenite, the drying in step (3) is carried out at 100 to 150° C. for 1 to 10 hours.
[0031] The invention also provides a mordenite obtained by the synthesis method.
[0032] Furthermore, the above-mentioned mordenite is a rectangular structure crystal with a crystal length of 500-1500nm, a width of 50-100nm, and a thickness of 30-60nm; the crystal has micron characteristics in the length direction and nanometer characteristics in the width and thickness directions, wherein the main pores of the mordenite are distributed in the length direction of the crystal, and the size of the main pores is 0.65×0.70nm, and the secondary pores of the mordenite are distributed in the width direction of the crystal, and the size of the secondary pores is 0.26×0.7nm.
[0033] Furthermore, the total specific surface area of the above-mentioned mordenite is 300 to 500 m 2 / g, pore volume is 0.1~0.4cm 3 / g,
[0034] Furthermore, the mordenite has a concentrated mesopore distribution, and the most probable pore diameter is 15 to 30 nm.
[0035] Compared with the existing methods, the mordenite and the synthesis method thereof provided by the present invention have the following advantages:
[0036] 1. The present invention provides a mordenite with micron-nano composite characteristics. Compared with the traditional micron-sized cake-shaped mordenite, when performing substance adsorption or catalytic reaction, the diffusion paths of substances in the two channels of the material are different. The material of the present invention has micron characteristics in the length direction and nano characteristics in the width and thickness directions. The main channels of mordenite are distributed in the length direction of the crystal, and the secondary channels of mordenite are distributed in the width direction of the crystal. Therefore, the mordenite of the present invention can show unique advantages and characteristics in adsorption and catalysis.
[0037] 2. The method for synthesizing mordenite provided by the present invention includes a two-stage crystallization reaction process, wherein the first-stage crystallization reaction is mainly to ensure the nucleation process of mordenite, and then the additives sulfate and lignin sulfonate are introduced in the second-stage crystallization process, and the comprehensive regulation of the two-stage crystallization reaction conditions (reaction temperature and reaction time) is matched. On the one hand, in the mordenite crystal growth stage, the added lignin sulfonate will be adsorbed on the specific crystal surface of the zeolite, inducing the synthesis to obtain mordenite crystals with specific morphology, and the introduction of sulfate will further promote the interaction between lignin sulfonate and zeolite crystals. The present invention introduces lignin sulfonate and sulfate in the second-stage crystallization process, which can ensure that a mordenite product with a specific structure is obtained on the one hand, and on the other hand, avoid the influence of the introduced lignin sulfonate and sulfate on the nucleation process of the molecular sieve, and avoid the problem of not being able to obtain a mordenite product. Because the nucleation stage is a crucial link in the molecular sieve synthesis process, the introduction of additives has a huge impact on the nucleation process. If the introduced additives do not match the reaction system, nucleation will be prevented, and mordenite cannot be synthesized or the product contains a large amount of impurities. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a SEM photograph of the mordenite obtained in Example 1 of the present invention.
[0039] Figure 2 This is the pore size distribution diagram of the mordenite obtained in Example 1 of the present invention.
[0040] Figure 3 This is a SEM photograph of the mordenite obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The technical scheme and effect of the present invention are further described below in conjunction with the embodiments, but are not limited to the following embodiments. In the present invention, wt% is mass fraction.
[0042] The specific surface area and other pore structure parameters of the sample in the present invention are measured by low temperature nitrogen adsorption method, and the ASAP2400 physical adsorption instrument produced by Micromeritics Instruments is used for testing and characterization. Before the measurement, the sample is vacuum treated at 300°C for more than 4 hours. The total specific surface area is calculated according to the BET isotherm equation, and the pore size distribution is calculated using the BJH method.
[0043] The microscopic morphology of the samples in the present invention was characterized by scanning electron microscopy: a JSM-6 301F scanning electron microscope (equipped with Oxford EDS) manufactured by JEOL Ltd. was used, with an operating voltage of 20 kV, a working distance of 15 mm, and a resolution of 1.5 nm.
[0044] The crystal structure of the sample in the present invention is characterized by an X-ray diffractometer, using a Japanese Rigaku D / max2500 X-ray diffractometer, a Cu target, a Kα radiation source, a graphite monochromator, a tube voltage of 40 kV, a tube current of 80 mA, a scanning range of 5° to 40°, a step size of 0.1°, and a scanning speed of 1° / min.
[0045] Example 1
[0046] Take a clean beaker, take 0.43g sodium hydroxide, 0.22g mordenite seed, 35g deionized water and mix them evenly, react at 130℃ for 3h; after cooling, mix them evenly with 3.2g white carbon black and 1.0g aluminum nitrate nonahydrate, age at 30℃ for 6h; then react at 160℃ for 4h; after the reaction, lower the temperature to 25℃, then add 0.43g potassium sulfate and 0.23g sodium lignin sulfonate, react at 145℃ for 45h; then filter the obtained sample 5 times, and then place it in an oven at 130℃ for 10h. The obtained sample is numbered M1, and the sample properties are shown in Table 1. From the SEM photos (see Figure 1 ) It can be seen that the crystal morphology of the sample is a rectangular columnar crystal. The length of the rectangular crystal is about 500-1500nm, the width is 50-100nm, and the thickness is about 30-60nm, which has micron and nano composite properties.
[0047] Example 2
[0048] Take a clean beaker, take 0.53g of sodium hydroxide, 0.16g of mordenite seed, and 24g of deionized water, mix them evenly, and react at 100℃ for 5h; after cooling, mix them evenly with 1.6g of silica gel and 1.0g of aluminum nitrate nonahydrate, and age them at 20℃ for 10h; then react at 190℃ for 10h; after the reaction, lower the temperature to 25℃, then add 0.16g of potassium sulfate and 0.08g of potassium lignin sulfonate, and react at 170℃ for 17h; then filter the obtained sample 5 times, and then place it in an oven at 130℃ for 10h. The obtained sample is numbered M2, and the sample properties are shown in Table 1.
[0049] Example 3
[0050] Take a clean beaker, take 0.16g of sodium hydroxide, 0.064g of mordenite seed, and 47g of deionized water, mix them evenly, and react at 200℃ for 1h; after cooling, mix them evenly with 6.4g of silica gel and 1.0g of aluminum nitrate nonahydrate, and age them at 40℃ for 5h; then react at 150℃ for 3h; after the reaction, lower the temperature to 25℃, then add 1.28g of potassium sulfate and 0.64g of potassium lignin sulfonate, and react at 140℃ for 55h; then filter the obtained sample 5 times, and then place it in an oven at 130℃ for 10h. The obtained sample is numbered M3, and the sample properties are shown in Table 1.
[0051] Example 4
[0052] Take a clean beaker, take 0.35g potassium hydroxide, 0.08g mordenite seed, and 30g deionized water, mix them evenly, and react at 160℃ for 3h; after cooling, mix them evenly with 5g silica gel and 0.8g aluminum chloride, and age at 35℃ for 5h; then react at 165℃ for 5h; after the reaction, lower the temperature to 25℃, then add 0.7g sodium sulfate and 0.35g potassium lignin sulfonate, and react at 150℃ for 45h; then filter the obtained sample 5 times, and then place it in an oven at 130℃ for 10h. The obtained sample is numbered M4, and the sample properties are shown in Table 1.
[0053] Example 5
[0054] Take a clean beaker, take 0.26g potassium hydroxide, 0.12g mordenite seed, 35g deionized water, mix evenly, and react at 170℃ for 2h; after cooling, mix evenly with 4.3g white carbon black and 0.75g aluminum chloride, and age at 37℃ for 9h; then react at 153℃ for 7h; after the reaction, lower the temperature to 25℃, then add 0.6g sodium sulfate and 0.3g sodium lignin sulfonate, and react at 143℃ for 43h; then filter the obtained sample 5 times, and then place it in an oven at 130℃ for 10h. The obtained sample is numbered M5, and the sample properties are shown in Table 1.
[0055] Comparative Example 1
[0056] Take a clean beaker, take 0.43g sodium hydroxide, 0.22g mordenite seed, 35g deionized water and mix them evenly, react at 130℃ for 3h; after cooling, mix them evenly with 3.2g white carbon black, 1.0g aluminum nitrate nonahydrate, 0.43g potassium sulfate, 0.23g sodium lignin sulfonate, and age at 30℃ for 6h; then react at 160℃ for 4h; after the reaction, lower the temperature to 25℃, and then react at 145℃ for 45h; then filter the obtained sample 5 times, and then place it in an oven at 130℃ for 10h to dry. The obtained sample is numbered M6, and the sample properties are shown in Table 1. The obtained sample is an intangible substance, indicating that the direct addition of lignin will affect the nucleation of the molecular sieve and make the raw material unable to crystallize.
[0057] Comparative Example 2
[0058] Take a clean beaker, take 0.43g sodium hydroxide, 0.22g mordenite seed, 35g deionized water, 3.2g white carbon black, 1.0g aluminum nitrate nonahydrate and mix them evenly, age at 30℃ for 6h; then react at 160℃ for 49h; then filter the obtained sample 5 times, and then place it in an oven at 130℃ for 10h. The obtained sample is numbered M7. The sample properties are shown in Table 1, and its SEM photo is shown in Figure 2 From the SEM photos, it can be seen that the morphology of the molecular sieve obtained by the conventional method is a single crystal with large particles of micrometer scale.
[0059] Comparative Example 3
[0060] Take a clean beaker, take 0.43g of sodium hydroxide, 0.22g of mordenite seed crystals, and 35g of deionized water, mix them evenly, and react at 130℃ for 3h; after cooling, mix them evenly with 3.2g of white carbon black and 1.0g of aluminum nitrate nonahydrate, and age at 30℃ for 6h; then react at 160℃ for 4h; after the reaction, lower the temperature to 25℃, then add 0.23g of sodium lignin sulfonate, and react at 145℃ for 45h; then filter the obtained sample 5 times, and then place it in an oven to dry at 130℃ for 10h. The obtained sample is numbered M8, and the morphology of the obtained molecular sieve is micron-scale large-particle single crystals.
[0061] Comparative Example 4
[0062] Take a clean beaker, take 0.43g of sodium hydroxide, 0.22g of mordenite seed, and 35g of deionized water, mix evenly, and react at 130℃ for 3h; after cooling, mix evenly with 3.2g of white carbon black and 1.0g of aluminum nitrate nonahydrate, and age at 30℃ for 6h; then react at 160℃ for 4h; after the reaction, lower the temperature to 25℃, and then add 0.43g of potassium sulfate and react at 145℃ for 45h; then filter the obtained sample 5 times, and then place it in an oven at 130℃ to dry for 10h. The obtained sample is numbered M9, and the morphology of the obtained molecular sieve is micron-scale large-particle single crystal.
[0063] Table 1 Properties of samples of Examples and Comparative Examples
[0064]
[0065] Note: The crystallinity of the molecular sieve in Example 1 is taken as a reference and is set to 100%. The crystallinity of all samples is obtained by comparing with the crystallinity of this sample.
Claims
1. A method for synthesizing mordenite, comprising the following contents: (1) Under contact conditions, mordenite seed crystals, inorganic alkali and water are mixed for heat treatment, and after cooling to 20-30° C., silicon source and aluminum source are added for aging treatment; (2) heating the material obtained after the aging treatment in step (1) to perform a first-order crystallization reaction; (3) After the first-order crystallization reaction is completed and the temperature is lowered to 10-30°C, sulfate and lignin sulfonate are added and the temperature is raised to carry out a second-order crystallization reaction, and then the mordenite is obtained by separation and drying.
2. The method for synthesizing mordenite according to claim 1, characterized in that: The inorganic base in step (1) is one or more of sodium hydroxide and potassium hydroxide.
3. The method for synthesizing mordenite according to claim 1, characterized in that: The heat treatment in step (1) is carried out at 100 to 200° C. for 1 to 5 hours.
4. The method for synthesizing mordenite according to claim 1, characterized in that: The aluminum source in step (1) is selected from one or more of aluminum sulfate, sodium aluminate, aluminum chloride and aluminum nitrate.
5. The method for synthesizing mordenite according to claim 1 or 4, characterized in that: The aluminum source in step (1) is aluminum chloride and / or aluminum nitrate.
6. The method for synthesizing mordenite according to claim 1, characterized in that: The silicon source in step (1) is selected from one or more of silica gel, white carbon black, silica sol and water glass.
7. The method for synthesizing mordenite according to claim 1, characterized in that: The molar ratio of the inorganic base, silicon source, aluminum source and water in step (1) is 2-12 inorganic base: 18-90 SiO2: A12O3: 800-2300 H2O.
8. The method for synthesizing mordenite according to claim 1 or 7, characterized in that: The molar ratio of the inorganic base, silicon source, aluminum source and water in step (1) is 3-10 inorganic base: 20-80 SiO2: A12O3: 1000-2000 H2O.
9. The method for synthesizing mordenite according to claim 1, characterized in that: The aging treatment temperature in step (1) is 10 to 50° C. and the aging treatment time is 2 to 15 hours.
10. The method for synthesizing mordenite according to claim 1 or 9, characterized in that: The aging treatment temperature in step (1) is 20 to 40° C. and the aging treatment time is 5 to 10 hours.
11. The method for synthesizing mordenite according to claim 1, characterized in that: The mass ratio of the mordenite seed crystals to the silicon source in step (1) is 0.5 to 12:
100.
12. The method for synthesizing mordenite according to claim 1 or 11, characterized in that: The mass ratio of the mordenite seed crystals to the silicon source in step (1) is 1 to 10:
100.
13. The method for synthesizing mordenite according to claim 1, characterized in that: The reaction temperature of the first-stage crystallization reaction in step (2) is 140-200° C.; the first-stage crystallization reaction time is 3-12 hours.
14. The method for synthesizing mordenite according to claim 1 or 13, characterized in that: The reaction temperature of the first-stage crystallization reaction in step (2) is 150-190° C.; the first-stage crystallization reaction time is 5-10 hours.
15. The method for synthesizing mordenite according to claim 1, characterized in that: The lignin sulfonate in step (3) is at least one of sodium lignin sulfonate and potassium lignin sulfonate.
16. The method for synthesizing mordenite according to claim 1, characterized in that: The sulfate in step (3) is at least one of sodium sulfate, potassium sulfate, iron sulfate, copper sulfate and magnesium sulfate.
17. The method for synthesizing mordenite according to claim 1 or 16, characterized in that: The sulfate in step (3) is at least one of sodium sulfate and potassium sulfate.
18. The method for synthesizing mordenite according to claim 1, characterized in that: The mass ratio of lignin sulfonate to silicon source in step (3) is 0.03-0.15:
1.
19. The method for synthesizing mordenite according to claim 1 or 18, characterized in that: The mass ratio of lignin sulfonate to silicon source in step (3) is 0.05-0.1:
1.
20. The method for synthesizing mordenite according to claim 1, characterized in that: The mass ratio of sulfate to silicon source in step (3) is 0.1-0.2:
1.
21. The method for synthesizing mordenite according to claim 1, characterized in that: The reaction temperature of the second-stage crystallization reaction in step (3) is 130-190° C.; the second-stage reaction time is 15-55 h.
22. The method for synthesizing mordenite according to claim 1 or 21, characterized in that: The reaction temperature of the second-order crystallization reaction in step (3) is 140-180° C.; the second-stage reaction time is 17-50 h.
23. The method for synthesizing mordenite according to claim 1, characterized in that: The reaction temperature of the second-stage crystallization reaction in step (3) is 5 to 25° C. lower than the reaction temperature of the first-stage crystallization reaction in step (2).
24. The method for synthesizing mordenite according to claim 1 or 23, characterized in that: The reaction temperature of the second-stage crystallization reaction in step (3) is 10 to 20° C. lower than the reaction temperature of the first-stage crystallization reaction in step (2).
25. The method for synthesizing mordenite according to claim 1, characterized in that: The drying in step (3) is carried out at 100 to 150° C. for 1 to 10 hours.
Citation Information
Patent Citations
Microwave-assisted method for synthesizing MOR zeolite molecular sieve membrane for dilute solution
CN105366689A
Synthesis method for nanometer MOR molecular sieve
CN106698453A
Method for synthesizing mordenite (MOR) molecular sieve as well as product and application of molecular sieve
CN108217680A
Synthesizing method for MOR zeolite comprising zinc
CN1524788A
Green synthesis method for regulating morphology of mordenite molecular sieve
CN112850743A